ANALISIS MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DALAM ORGANISASI - Joko Puji Rahmanto; Finisica Dwijayanti Ptrikha; Siti Sri Wulandari; Harti; Tri Sudarwanto (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2021)
Communication is the sending of information or messages to related parties. 80% of the skills or competencies needed are soft skills. 49% of soft skills are skills or abilities that must be present in each employee, namely basic communication skills. communication skills are not only used in work, but communication skills are also needed in the field, considering that communication skills are a point of the 21st century. Improving students' communication skills can be done through learning activities. These efforts can be carried out in several ways, namely the application of learning models that are useful to support communication skills in students. Many models that can be applied in learning are in the form of project-based learning models. The model applied in this research is a literature review (literature analysis). The PBL learning model can improve students' communication skills.